Multidimensional Performance Measurement Based on Social Return on Investment (SROI) in Sustainable Spring Management Systems - Matheus Nugroho; Yustinus Budi Hermanto; M. Imron Mas’ud (JTI: Jurnal Teknik Industri, 2026)
This study aims to develop and apply a multidimensional performance measurement framework based on Social Return on Investment (SROI) to evaluate the sustainability and productivity of spring management systems. A mixed-method approach was employed using an extended six-stage SROI framework integrating economic, social-institutional, environmental, cultural-spiritual, and health-wellbeing dimensions. Data were collected from 187 stakeholders through structured surveys, in-depth interviews, focus group discussions, 18 months of participatory observation, spring discharge measurements, and secondary data sources. The novelty of this research lies in the integration of the Sustainable Livelihoods Framework and Social-Ecological Systems perspective into a multidimensional SROI model capable of capturing both market and non-market values, including cultural and social benefits. The results reveal an SROI ratio of 4.1:1, indicating that every unit of investment generated 4.1 units of social value. Economic impacts contributed 44% of the total benefits, followed by social-institutional (31%), environmental (18%), and cultural-spiritual (7%) dimensions. Productivity improvements were reflected through increased household income, reduced resource access time, enhanced ecosystem services, and strengthened local governance. The study demonstrates that sustainable spring management depends not only on ecological restoration but also on social capital and cultural engagement. This framework provides a comprehensive decision-support tool for assessing sustainability performance and guiding evidence-based conservation policies.